2023
DOI: 10.3390/pr11030801
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study and Molecular Simulation of the Effect of Temperature on the Stability of Surfactant Foam

Abstract: Temperature changes in CO2 foam-fracturing construction can easily affect surfactant foam stability. To investigate the effect of temperature on the foam stability of different types of surfactants, this study measured the foam half-life and viscosity of four typical surfactants, CTAB, LAS-30, HSB1214, and TX-10, using a novel self-designed and built foam performance measurement device. The effects of temperature on foam half-life and viscosity were studied. The results show that as the temperature increased, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Similarly, Yan and Zhang highlighted the importance of foam stability, as measured by HLT, in reducing foam mobility within the porous media of oil reservoirs . Furthermore, temperature changes can also affect foam stability, as highlighted by Nie et al The data revealed an interesting trend regarding the impact of CO 2 gas flow rate on foam HLT. Increasing the flow rate from 1 lpm to 2 lpm resulted in a decrease in HLT for the lowest SDS concentration (0.5 wt %), with HLT dropping from 143 s at 1 lpm to 96 s at 2 lpm.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Yan and Zhang highlighted the importance of foam stability, as measured by HLT, in reducing foam mobility within the porous media of oil reservoirs . Furthermore, temperature changes can also affect foam stability, as highlighted by Nie et al The data revealed an interesting trend regarding the impact of CO 2 gas flow rate on foam HLT. Increasing the flow rate from 1 lpm to 2 lpm resulted in a decrease in HLT for the lowest SDS concentration (0.5 wt %), with HLT dropping from 143 s at 1 lpm to 96 s at 2 lpm.…”
Section: Resultsmentioning
confidence: 99%